Urbanisation, migration, depopulation and virtual ritual community - the village kurban as a shared meal - Hristov Petko; Manova Tsvetana (Balcanica)
The paper deals with the specific use of collective rituals focused on blood sacrifice and a shared meal among Orthodox Christians in the Balkans, known mostly as kurban. In studying a variety of feasts, the analytical focus is on the collective gathering and the shared meal, which is celebrated by the small village community as its “homeland”, a sense of belonging to a virtual community consisting of people from all over the world. This paper pays particular attention to examples of the collective kurban in depopulated villages. Among migrants in big cities born in the same village, the kurban is understood as part of a common cultural heritage and a ritual that helps produce and/or re-produce a group identity within a broader national framework and urban social milieu. The kurban is also perceived by the participants as a ritual way of creating social cohesion for kinship-based and territory-based communities, beyond confessional attachment. In a selection of cases, the paper demonstrates how a blood sacrifice and a shared meal, as well as the symbolic use of the patron saint of a birthplace, recreates cohesion between the former members and the new migrants from the city to the village.